Analisis Perlindungan Hak Pada Manusia, Terhadap Anak Yang Menjadi Korban Bullying - Faturohman Faturohman; Badrudin Badrudin; Khujaemi Saputra (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
Human rights, these are rights that humans have, in several countries there are discussions about the rights of children who are victims of bullying. There is legislation that discusses this right, children have the right to be protected from all forms of violence, bullying is behavior that is degrading. The rise of this case in Indonesia has had a negative impact on victims, perpetrators and sanctions, but it has had a very serious impact on the victims. The factor that causes cases of bullying is that when there is no adequate supervision from adults in the school environment, at home, or in other public places, perpetrators of bullying can feel that they can do it without consequences. Therefore, cases of bullying must be prevented and monitored very closely, so that there are no more cases of this increasing over time.